A CRITICAL DISCOURSE ANALYSIS OF INDONESIA PRESIDENTIAL ELECTION IN 2014 GIVING SPEECHES IN CAMPAIGN DEBATE - Ikhwan Persada; Jufri Syahrudin (English Language and Literature, 2018)
This Paper is intended to show how one a single reality, that is International Politics and National Resilience, is presented and viewed by the two major of presidential candidates in 2014. In this paper, van Dijk’s (2004) framework adopted form Politics, ideology and discourse is used identify the discursive structures within the transcription of political campaign debate and to find out the ideology underlying them. The macro strategies of ‘positive self-representation’ and ‘negative other-representation’ (which are intimately tied up with ‘Polarization’ of in group vs. out group ideologies or US-THEM) and more strategies become very accurate criteria for the evaluation of attitudes, and opinions. The findings of this study can conducive to expanding readers’ critical thinking abilities in comprehension and production of language.